Towards a Model of an Integrated Social Studies Curriculum: A Sample Learning Unit - Villanueva, Juliet Aleta R. (Alipato, A Journal of Basic Education; Vol 3 No 2 (2008), 2025)
The Social and Human Sciences Committee of the UNESCO National Commission of the Philippines (UNACOM) and the Philippine Social Science Council (PSSC) recently published the draft of the Social Studies Curriculum for Basic Education which strongly recommends that the basic education curriculum be geared toward integration or "interdisciplinarity" within Social Studies and across other core subjects. This study responds to UNACOM and PSSC’s call for an integrated curriculum in Social Studies for the elementary school from the perspective of a teacher-practitioner. This paper primarily describes an integrated social studies curriculum developed and implemented in an international school in the Philippines. The features and content of this curriculum were examined through a sample learning unit. Work over this curriculum attempts to provide a model in developing an integrated Social Studies for basic education.